Evidence Based Case Report on Homoeopathic Treatment of Pityriasis Versicolor - Rai, Satya Prakash; Khare, Anshita; Mishra, Sanskriti (Journal for Research in Applied Sciences and Biotechnology, 2024)
Pityriasis Versicolor is a common fungal skin infection[1]. It’s sometimes also called as Tinea versicolor. Pityriasis versicolor causes patches of skin to change colour. The patches usually occur on the chest, upper back, upper arms, neck or tummy. The patches are flat and round and can join up to form large areas. They may look scaly and can sometimes be itchy[2]. It is a case report on pityriasis versicolor. On first visit, the patient was having white coloured spots on neck and upper chest area. Symptomatology was erected after taking the case properly and repertorization was done by synthesis repertory. The medicine was prescribed in centesimal potency and patient was better with in 3 months.